Capacity Building Workshop on Genetic Resource Policies for CGIAR Scientists and Partners in East Africa, 4 - 7 June 2019, ILRI Campus, Addis Ababa, Ethiopia - CGIAR Genebank Platform (Bioversity International, 2019)
The CGIAR Genebank Platform Policy Module, in coordination with the International Livestock Research Institute (ILRI), organized the ‘Capacity building workshop on genetic resource policies for CGIAR scientists and partners in East Africa’. The workshop was held from 4 - 7 June 2019, at the ILRI campus in Addis Ababa, Ethiopia. This event brought together 30 staff members from 6 CGIAR Centres and 10 participants from national agricultural research organizations in Democratic Republic of the Congo, Ethiopia, Kenya, Uganda and Zimbabwe. The workshop was designed to increase participants’ understanding of the CGIAR Centres’ and national research organizations’ obligations vis-à-vis international treaties and conventions dealing with access and benefit-sharing, and how these international instruments influence the day-to-day management of the collections. The workshop included participatory analyses of practical case studies and hypothetical scenarios where the interface between the Nagoya Protocol on Access and Benefit Sharing and the ITPGRFA (Plant Treaty) can raise legal and procedural issues. It also addressed the management of information associated with genetic resources including digital sequence information.